Vibrations when drilling wells for oil and gas - Kobeza, V. S.; Khomenko, V. L. (НТУ ДП, 2022)
The article discusses the causes of drill string vibrations when drilling oil and gas wells. It was established that they can be divided into three large groups: geological, technical and technological. The harmful effect of vibrations on the technological process of drilling wells, the operation of drilling equipment and tools is considered. The column of drill pipes operating in the well is an elastic system, in the lower part it is supported by a bit on the bottom of the well, and in the upper part it is fixed in the rotor. Under the influence of the torque and the load, this system resembles a spring with a large step between turns, the value of which depends on the forces acting on the column, as well as on the diameter of the well. While rotating, such an elastic loaded system experiences various forms and modes of oscillations, the deviation of its axis from the axis of the well, the angle of rotation and the range of oscillations change periodically. Oscillating processes of the drill string are called vibrations. The vibration mode is characterized by the number of oscillations per unit of time (frequency) and the largest deviation of the column from the axis of the well (amplitude), as well as the range of oscillations corresponding to the doubled amplitude; the inverse of the frequency is called the oscillation period (the time between two successive identical states of the system). When the frequency of forced disturbing forces coincides with the frequency of natural oscillations of the column, resonant phenomena occur, the amplitude and frequency of oscillations increase and vibration appears. The frequency of rotation of the column, which leads to resonance, is called critical.
Keywords: буріння свердловин; буріння газових свердловин; буріння нафтових свердловин